Wolf expansion and its effect on parasitic infections - Elisa Fesce; Nicola Ferrari (2024)
Echinococcus spp. are parasitic cestodes that have a dixenic life cycle, involving definitive hosts (typically canids) and intermediate hosts (including herbivores and rodents). Humans can become infected with Echinococcus spp., leading to significant health issues such as organ dysfunction, anaphylaxis, or even death. Echinococcus spp., particularly Echinococcus granulosus and Echinococcus multilocularis, pose substantial health risks, thereby representing a global public health challenge. Among carnivores, foxes (Vulpes spp.) and wolves (Canis lupus) play crucial but distinct roles in the life cycle of the parasite. Both species act as definitive hosts, harboring adult parasites in their intestines, excreting parasite eggs in their feces, and serving as sources of infection for intermediate hosts. Despite these similarities, they differ in predatory behavior and habitat, which can influence transmission dynamics. Wolves are larger pack animals that primarily prey on larger herbivores, whereas foxes are more solitary and opportunistic feeders, often consuming small mammals and scavenging. In recent decades, wolf populations have significantly expanded across Italy, particularly in the Apennine and Alpine regions. This expansion may alter local ecological dynamics and change the roles of both species in disease transmission. To explore the effects of wolf expansion on Echinococcus spp. prevalence, we developed a set of mathematical models based on the predator-prey framework. These models explicitly include mechanisms of infection transmission, allowing us to predict future scenarios of parasite transmission in wildlife. We simulated host-parasite dynamics in a fox population without wolves, then introduced two wolves into the area to examine how, and under what conditions, this introduction could alter parasite-host dynamics and Echinococcus spp. prevalence. Our results confirmed that, without host mortality due to parasite presence, the two host species reach a new equilibrium, modulating the populations of ...